Effect of Antimicrobial Exposure on AcrAB Expression in Salmonella enterica Subspecies enterica Serovar Choleraesuis - Usui, Masaru; Nagai, Hidetaka; Hiki, Mototaka; Tamura, Yutaka; Asai, Tetsuo (Frontiers in Microbiology, 2013)
Understanding the impact of antimicrobial use on the emergence of resistant bacteria is imperative to prevent its emergence. For instance, activation of the AcrAB efflux pumps is responsible for the emergence of antimicrobial-resistant Salmonella strains. Here, we examined the expression levels of acrB and its multiple regulator genes (RamA, SoxS, MarA, and Rob) in 17 field isolates of S. Choleraesuis by using quantitative PCR methods. The expression of acrB increased in 8 of the field isolates (P < 0.05). The expression of acrB was associated with that of ramA in 1 isolate, soxS in 1 isolate, and both these genes in 6 isolates. Thereafter, to examine the effect of selected antimicrobials (enrofloxacin, ampicillin, oxytetracycline, kanamycin, and spectinomycin) on the expression of acrB and its regulator genes, mutants derived from 5 isolates of S. Choleraesuis were selected by culture on antimicrobial-containing plates. The expression of acrB and ramA was higher in the mutants selected using enrofloxacin (3.3–6.3- and 24.5–37.7-fold, respectively), ampicillin (1.8–7.7- and 16.1–55.9-fold, respectively), oxytetracycline (1.7–3.3- and 3.2–31.1-fold, respectively), and kanamycin (1.6–2.2- and 5.6–26.4-fold, respectively), which are AcrAB substrates, than in each of the parental strains (P < 0.05). In contrast, in AcrAB substrate-selected mutants, the expression of soxS, marA, and rob remained similar to that in parental strains. Of the 4 antimicrobials, the level of ramA expression was significantly higher in the enrofloxacin- and ampicillin-selected mutants than in the oxytetracycline- and kanamycin-selected mutants (P < 0.05), whereas the expression levels of acrB and multiple regulator genes in spectinomycin-selected mutants were similar to those in each parental strain. These data suggest that exposure to antimicrobials that are AcrAB substrates enhance the activation of the AcrAB efflux pump via RamA, but not via SoxS, MarA, or Rob in S. Choleraesuis.